Reduction of output common mode voltage using a novel SVM implementation in matrix converters for improved motor lifetime - Espina, Jordi; Ortega, Carlos; De Lillo, Liliana; Empringham, Lee; Balcells, Josep; Arias, Antoni (Institute of Electrical and Electronics Engineers, 2014)
This paper presents the study of an alternative Space Vector Modulation (SVM) implementation for Matrix Converters (MC) which reduces the output Common Mode (CM) voltage. The strategy is based on replacing the MC zero vectors by the rotating ones. In doing this, the CM voltage can be reduced which in-turn reduces the CM leakage current. By reducing the CM current, which flows inside the motor through the bearings and windings, the Induction Motor (IM) deterioration can be slowed down. The paper describes the SVM pattern and analyses the CM voltage and the leakage current paths. Simulation and experimental results based on a MC-IM drive are provided to corroborate the presented approach.